KAJIAN MORPHOMETRI PADA SATUAN WILAYAH PENGELOLAAN DAS PRIORITAS DI KOTA PADANG (STUDI KASUS PADA DAS ARAU, DAS KURANJI, DAN DAS AIR DINGIN) - Lusi Utama (Ensiklopedia of Journal, 2022)
In line with the sustainable development process, it is necessary to regulate activities with the main priority to re-create the ecological balance of the environment. The three rivers which were expected to receive rainfall, such as Batang Kuranji, Batang Arau and Batang Air Dingin, were unable to cope with the flooding. The hydrological conditions of the 3 watersheds are currently experiencing changes in hydrological characteristics which are marked by increased flood potential. This threat, apart from natural factors such as climate and extreme rainfall, can also occur due to human factors such as cultivating floodplain areas, land allocations in flood plains that are not in accordance with land functions. Changes in land use in an area can affect the function of the water system. This is in accordance with the opinion of Arsyad (2010), which states that any treatment given to a plot of land can affect the water system in that place and places downstream. From the above threat parameters, flooding is also strongly influenced by natural phenomena in the form of morphometry consisting of watershed area, watershed shape, river network, flow density, flow pattern, land use and river steepness gradient. For this reason, research on watershed morphometry needs to be carried out so that the causes of flooding in the watershed can be identified. Floods that occurred from 2016 to 2021, have harmed the community. By using Paimin's theory for morphometry, the ARC GIS program to determine the extent of flooding, as well as Thiessen's theory to determine rainfall and a rational theory to analyze discharge, it was obtained into 3, namely the Arau watershed, Kuranji watershed and Air Dingin watershed prone to flooding with the highest score due to the use of land.